“ОСТОНА” ЛИНГВОМАДАНИЙ БИРЛИГИНИНГ ИЧКИ МАЪНО ВАЛЕНТЛИГИ - Махмудова, С.Х. (SCIENCE and SOCIETY, 2021)
The article is devoted to the analysis of the linguocultural units of the Uzbek language “Ostona” (Threshold). The object of the research is “Ufk”*( Dawning) by the famous writer Said Ahmad and “Vaqt”(Time) by Gafur Gulyam. The main aim of the research is to find linguoculturems in the texts of works, the meanings of which are not reflected in modern explanatory dictionaries.
Keywords: linguocultural unity; valence; concept; “Golden book”; gate of life; fear of life; equivalent; kuevnavkars